Reliability of Pterygium Redness Grading Software (PRGS) in describing different types of primary pterygia based on appearance = Kebolehpercayaan Perisian Penggredan Kemerahan Pterigium (PRGS) dalam mengelaskan pelbagai jenis pterigium berdasarkan perawakan - Hilmi, Mohd Radzi; Che Azemin, Mohd Zulfaezal; Mohd Kamal, Khairidzan; Ariffin, Azrin Esmady; Abdul Rahim, Muhammad Afzam Shah; Mohd Tamrin, Mohd Izzuddin (Universiti Kebangsaan Malaysia, 2020)
he aim of this study was to evaluate the reliability of Pterygium Redness Grading Software (PRGS) in describing different types of primary pterygia. Ninety-three participants with primary pterygia who visited an ophthalmology clinic were recruited in this study. PRGS is a semi-automated computer program used to measure fibrovascular pterygium redness by analysing digital images of the pterygium and grading it on a continuous scale of 1 (minimum redness) to 3 (maximum redness). An ocular surface expert graded all 93 images in random order. The reliability of PRGS was determined by comparing pterygium redness measured using the software and by the expert. The mean and standard deviation of redness of pterygium fibrovascular images measured using PRGS and by the expert were 1.81 ± 0.58 and 1.73 ± 0.61, respectively (P = 0.396). A comparative analysis based on pterygium type showed an increase in redness according to pterygium type (Type I: 1.43 ± 0.32; Type II: 1.67 ± 0.55; and Type III: 2.31 ± 0.46), without significant differences compared to redness measured by the expert (Type I: 1.38 ± 0.34; Type II: 1.78 ± 0.62; and Type III: 2.02 ± 0.66) (all P > 0.05). PRGS could describe and classify pterygia according to their redness, and PRGS-based classification was in agreement with the the established classification of pterygia. Therefore, PRGS can be used in addition to the existing pterygium grading system. ******************************************************************************* Matlamat kajian ini adalah untuk menilai kebolehpercayaan Perisian Penggredan Kemerahan Pterygium (PRGS) dalam mengelaskan jenis-jenis pterigium primer. Kajian ini berjaya merekrut 93 pesakit daripada klinik oftalmologi yang menghidap pterigium primer. PRGS merupakan program komputer semi-automatik yang berfungsi untuk mengukur darjah kemerahan pterigium fibrovaskular yang diperoleh daripada imej digital pterigium, dalam bentuk pengredan berterusan (1 untuk kemerahan minimum dan 3 untuk kemerahan maksimum). Kesemua 93 imej pterigium telah digredkan secara rambang oleh pakar permukaan okul. Kebolehpercayaan PRGS telahpun ditentukan dengan membandingkannya dengan kemerahan yang dicerap oleh pakar. Nilai min dan sisihan piawai untuk kemerahan pterigium fibrovaskular adalah 1.81 ± 0.58 (PRGS) dan 1.73 ± 0.61 (pakar), (P = 0.396). Analisis berasaskan jenis pterigium menunjukkan terdapat peningkatan kemerahan pterigium fibrovaskular apabila diukur menggunakan PRGS (Jenis I: 1.43 ± 0.32; Jenis II: 1.67 ± 0.55; Jenis III: 2.31 ± 0.46) berbanding pakar (Jenis I: 1.38 ± 0.34; Jenis II: 1.78 ± 0.62; Jenis III: 2.02 ± 0.66), tetapi perbezaan ini tidak signifikan untuk semua jenis pterigium (P > 0.05). Skala pengredan PRGS dapat mengelaskan pterigium berdasarkan kemerahan dan ia selaras dengan pengelasan pterigium sedia ada. Skala kemerahan ini boleh digunakan sebagai tambahan kepada pengredan pterigium yang sedia ada.